Of Mice and Men Opera Still - Ron Scherl:::Creator::::::::::::
The Spring Opera Theater production of Carlisle Floyd's "Of Mice and Men' opera adaptation. Richard J. Clark (Candy) stands to the left of William Neill (Lennie,) who sits with a puppy in his arms. On his right is Brent Ellis (George) on one knee.